1984
DOI: 10.1111/j.1432-1033.1984.tb07878.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of a thiol protease from rat liver nuclei

Abstract: A thiol protease was purified about 800-fold from the chromatin fraction of rat liver by employing Sepharose 6B gel filtration, chromatofocusing and Sephadex G-100 gel filtration. It was nearly homogeneous on sodium dodecyl sulfate/polyacrylamide gel electrophoresis and its molecular weight was about 29 000. The isoelectric point of the enzyme was 7.1. The pH optimum for degradation of 3H-labelled ribosomal proteins was 4.5. It is noticeable that the maximal activity was shifted to pH 5.5 by DNA, and that 30 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There is some confusion and contradiction as to the precise effects of protease inhibitors and it is likely that more than one protease is involved. It is of interest that Motizuki et al (1984) have reported the purification of a thiol protease from rat liver nuclei which was activated by DTT and inhibited by iodacetamide. The results of our study provide evidence that DCI and NEM may be targeting a critical thiol group which is essential for endonuclease activity and suggests that these compounds will be useful probes for further investigating this important element of the apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
“…There is some confusion and contradiction as to the precise effects of protease inhibitors and it is likely that more than one protease is involved. It is of interest that Motizuki et al (1984) have reported the purification of a thiol protease from rat liver nuclei which was activated by DTT and inhibited by iodacetamide. The results of our study provide evidence that DCI and NEM may be targeting a critical thiol group which is essential for endonuclease activity and suggests that these compounds will be useful probes for further investigating this important element of the apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Proteases which preferentially hydrolyze histones or other nuclear basic proteins in vitro have been isolated from the chromatin of various types of cells including spermatozoa. These enzymes may be involved in the metabolism of nuclear proteins (17,18), the modulation of higher order chromatin structures (7), and the control of gene expression. However, the capacity of an enzyme to hydrolyze histones in vifro is not enough to corroborate that the enzyme does hydrolyze histones in situ.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes may be involved in the metabolism of nuclear proteins (17,18), the modulation of higher order chromatin structures (7), and the control of gene expression. However, the capacity of an enzyme to hydrolyze histones in vifro is not enough to corroborate that the enzyme does hydrolyze histones in situ.…”
Section: Discussionmentioning
confidence: 99%
“…There is some confusion and contradiction as to the precise effects of protease inhibitors and it is likely that more than one protease is involved. In this respect it is of interest that Motizuki et al [32] have reported the purification of a thiol protease from rat liver nuclei which was activated by dithiothreitol and inhibited by iodacetamide.…”
Section: Discussionmentioning
confidence: 99%